La última red de protección social en España: prestaciones asistenciales y su activación - Arriba González de Durana, Ana; Pérez Eransus, Begoña (Política y Sociedad, 2008)
The concept of welfare states safety-net refers to those programmes that offer a means-tested guaranteed minimum income in the schemes for social protection. In the paper, we analyse the main developments followed by these policies in the last two decades in Spain. We distinguish two different trends that characterise two periods. In the first of them, the main schemes were introduced (PNCs and RMIs, mainly), broadening the coverage to non protected groups and leading to a low intensity safety-net that is also fragmented in different protection systems, but strongly ranked by the relationship that beneficiaries maintain with labour markets. The second period is characterized by the introduction of activation criteria in those protection schemes, a common, but not convergent, trend with other European welfare regimes. During the governments and international institutions as the EU have proposed activation programs as an efficient strategy to combat social exclusion. However, it have been raised questions related to their real purpose, integration or discouragement, and mainly related to their effectiveness in overcoming poverty and exclusion.